(untitled) (Russian Medical and Social Journal, 2019)
Introduction. Hypoparathyroidism after hyroidectomy is treated with oral calcium and vitamin-D supplements. Everyday prolonged use of calcium and vitamin D medications can lead sometimes to hypercalcemia that can cause Akute Kidney Injury (AKI) and Arterial Hypertension. We report on a clinical case of a man patient with postoperative hypoparathyroidism who presented with hypercalcemia, AKI and Chronic Kidney Disease (CKD) as a result of prolonged treatment with Dihydrotachysterol and calcium medications. Сlinical case. A male patient, 59 y.o., 11 years ago underwent total thyroidectomy, since that time was daily medicated with l-thyroxine 125-150 mcg, dihydrotachysterol 15 drops (approx. 0,62 mg), calcium in different forms without monitoring the blood and urine levels. He had high arterial pressure up to 200/120 mm Hg, treated with amlodipine 10 mg daily. After 5 years he took onemonth treatment with non-steroidal antiinflammatory drugs for pain relief because of a rib fracture. That time he underwent first AKI with full recovery. After 5 years a few AKI recurred with hypercalcemia. Dihydrotachysterol and calcium were cancelled, but since that time patient kept on getting non-prescribed Dihydrotachysterol and calcium in the same doses. After 1 year more in relapse series a puncture biopsy of the kidney showed nephrocalcinosis, chronic interstitial nephritis and CKD (С4А3) was diagnosed. The patient was treated successfully by dis-continuation of the above drugs, intravenous fluid administration and enhancement of calcium renal excretion. The patient is currently free of complaints for about 3 months. Сonclusion. It is important for clinicians to monitor calcium and 25-OH-D levels in blood serum during the prolonged treatment with calcium and vitamin D medications to prevent a hypercalcemia that can lead to AKI, CKD and other sever complications.